2016
DOI: 10.1007/s10854-016-4338-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of V2O5 nanorods grown by spray pyrolysis technique

Abstract: V 2 O 5 nanorods (NRs) were prepared by a chemical spray pyrolysis (CPS) onto heated glass substrates. The effects of vanadium solution concentration, deposition spray rate and substrate temperature on the structural, morphological and optical properties prepared thin films were investigated. X-ray diffraction (XRD) results indicated that the thin films have orthorhombic structures with preferential orientations along the (110) direction. Field emission scanning electron microscopy (FESEM) observations showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Among the various synthesis methods for nanostructured V 2 O 5 electrodes, ASPD has been recognized as the most effective nanostructure synthesis technique due to its easy process to synthesize, highly precise and controlled output product within a very short period, and less energy. [25,26] ASPD also offers inherent advantages over conventional SPT in terms of good control of stoichiometry, formation of various nanostructures, and the transparency of the electrode. [27] In this study, the authors presented a different method for the synthesis of 3D structured nanoporous V 2 O 5 transparent electrodes using the automatic spray pyrolysis deposition process.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various synthesis methods for nanostructured V 2 O 5 electrodes, ASPD has been recognized as the most effective nanostructure synthesis technique due to its easy process to synthesize, highly precise and controlled output product within a very short period, and less energy. [25,26] ASPD also offers inherent advantages over conventional SPT in terms of good control of stoichiometry, formation of various nanostructures, and the transparency of the electrode. [27] In this study, the authors presented a different method for the synthesis of 3D structured nanoporous V 2 O 5 transparent electrodes using the automatic spray pyrolysis deposition process.…”
Section: Introductionmentioning
confidence: 99%
“…Among the potential Vanadium Oxide compounds, the stable stage V 2 O 5 has a wide optical bandgap, good chemical and thermal stability, and exceptional thermoelectric properties, making it a likely candidate for use in a variety of sensors and photovoltaic applications. [8][9][10][11] The growth and development of both pure and Cd-doped V 2 O 5 are investigated in this work employing the spray pyrolysis process on glass as the substrate. Based on ionic radius compliance, Cadmium with an ionic radius of 1.44 A o has been considered a viable equivalent for Vanadium with an ionic radius of 1.34 A o .…”
Section: Introductionmentioning
confidence: 99%
“…These properties are highly dependent on crystallographic structure, crystal field splitting, and hybridization between O 2 p and V 3 d bands. [11,12] So far, various types of vanadium oxides, such as V 2 O 3 , [13][14][15] VO 2 , [16][17][18][19] and V 2 O 5 , [20][21][22] have been investigated to explore potential technological applications, and it is reported that VO 2 and V 2 O 5 can respond to ultraviolet (UV) light, which is expected to be solar blind or vacuum-UV detectors. [23][24][25][26][27] In particular, doped V 2 O 3 has attracted great attention in making high-performance electrodes.…”
Section: Introductionmentioning
confidence: 99%